Accounting for Topographic Effects on Snow Cover Fraction and Surface Albedo Simulations Over the Tibetan Plateau in Winter. (26th August 2022) - Miao, Xin; Guo, Weidong; Qiu, Bo; Lu, Sha; Zhang, Yu; Xue, Yongkang; Sun, Shufen
Abstract: The Tibetan Plateau (TP) is the highest land in the world and has a very complex topography. However, the influence of topography on TP snow cover simulations has not been adequately addressed in most land surface models. The analysis of satellite observations indicates that snow cover fraction (SCF) simulation biases increase with the topography complexity, and this increasing trend slows down when the standard deviation of topography is greater than 200 m. The result also shows that using the SCF schemes without consideration of topography leads to a consistent overestimation in winter. To account for the topographic effects, we introduce a modified topographic factor to the SCF schemes. Then we conduct regional simulations using the Simplified Simple Biosphere Model version 3 (SSiB3) and evaluate the results at the location of observation sites to reduce the uncertainty induced by forcing data. Compared with the default SCF scheme, the mean winter SCF bias is reduced from 3.83% to −0.10%. The optimization of SCF simulations further improves the winter surface albedo and land surface temperature (LST) simulations. The winter surface albedo bias over the TP is reduced from 0.020 to 0.007, with a maximum reduction by −0.133. The winter LST bias is reduced from −3.33 to −3.04 K, with a maximum reduction by 3.60 K. This study highlights the importance of topographic effects in simulating snow cover distribution and land surface energy budget for reducing the "cold bias" in winter climate simulations over the TP. Plain Language Summary: The Tibetan Plateau (TP) has a very complex topography, which greatly influences the snow cover distribution in winter. However, the influence of topography on snow cover simulations has not been adequately addressed in most land surface models. Based on the satellite data, we find that ignoring topography leads to a significant overestimation of the simulated snow cover distribution over the TP in winter, and the overestimation increases with the topographic complexity until the terrain complexity reaches a certain level. By applying this relationship, the winter snow cover distribution simulations are greatly improved over the TP, and this improvement further leads to the improvement of land surface energy budget simulations in winter. Taking the topographic effect on snow cover distribution into account contributes to reducing the "cold bias" in winter climate simulations over the TP. Key Points: The complex topography over the Tibetan Plateau greatly influences the snow cover distribution in winter Using the snow cover fraction (SCF) schemes without topography leads to a consistent positive bias of SCF simulations in winter By adding a topographic factor, the simulations of winter SCF and surface albedo are significantly improved